Kajian Terhadap Pembangunan Geotermal Di Pulau Flores Berdasarkan Prespektif Teori Keadilan (John Rawls) (Deposisi: Jurnal Publikasi Ilmu Hukum, 2023)
The potential for natural resources is very abundant, especially geothermal energy on Flores Island which is being sought after by investors. Apart from the very diverse diversity of the people. Therefore, the conflict that occurred on Flores Island resulted in rejection of the geothermal development project and how to analyze the protection of the rights of indigenous peoples on Flores Island based on the theory of justice (John Rawls). The research method used in this research is a normative juridical research method. This research is prescriptive in nature, offering a concept for solving a problem (problem solving) and not just descriptive (just to describe something as it is). The data sources used in this research are secondary data collected through literature (documentary research) and legal approaches. Traditional law communities on Flores Island always live side by side with nature. The country is supposed to protect its people through policies that are just and pro-people, but in reality at this time, their lives have been disturbed by the Geothermal Power Plant construction project carried out by the Indonesian government.